ABOUT THE NEED TO TEACH AL-FARABI TRIGONOMETRY IN THE SCHOOL COMPUTER SCIENCE AND MATHEMATICS EDUCATION SYSTEM - Akzholova, А.А.; Kamalova, Г.Б.; Khenner, Е.К.; Bayzakova, Е.М. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The trigonometric legacy of al-Farabi, the great thinker of the Middle Ages, who made an invaluable contribution to the development of world science and civilization, is of great theoretical and practical value. It offers unique algorithms for finding the sine of one degree and constructing trigonometric tables necessary for solving various practical tasks. Their inclusion in modern computer science and mathematics education will not only popularize the legacy of the great scientist, but also enrich the content of teaching trigonometry, strengthening its applied orientation, expand the system of subject knowledge of students in both mathematics and computer science, since the construction of a table is impossible without software implementation on a computer. Like the predominant part of al-Farabi's mathematical heritage, his works on trigonometry were first discovered and studied relatively recently by Audanbek Kubesov, a well-known Kazakh scientist in the field of the history of mathematics and pedagogy of the Islamic East. But the didactic potential of the trigonometric heritage of al-Farabi and the issues of its implementation in the educational process have not yet been investigated by anyone. The purpose of this work is to get acquainted with the trigonometric heritage of the great scientist and to study the possibility of introducing it into the system of school computer science and mathematics education.